Bimorph mirrors at synchrotron beamlines: from walking to flying. Issue 1 (1st December 2022) - Sutter, John P.; Alcock, Simon G.; Nistea, Ioana-Theodora; Signorato, Riccardo; Foster, Andrew; Sawhney, Kawal
Abstract: With brighter synchrotron sources, automated sample changers, and faster detectors, there is a strong scientific need for rapid and precise variation of the X-ray beam profile, rather than the "set and forget" operation of years past. Piezoelectric bimorph deformable mirrors already allow quick beam profile changes without the heat generation and wear of mechanical devices. Now, their early technological limitations – excessively constraining holders, progressive "junction effect" distortion, and communication bottlenecks with power supplies – are being overcome by a collaboration of scientists and engineers both in industry and at Diamond Light Source. A new generation of bimorph mirrors maintains a stable figure over extended periods of operation. Improved holders and flexible electrical connectors are greatly reducing the mechanical strain imparted to bimorphs, thereby improving their speed, accuracy, and stability. A more sophisticated high voltage power supply has on-board signal processing capacity, allowing large focusing changes within seconds and providing programmable time-varying voltage profiles to counteract piezoelectric creep. The communication between beamline systems and power supplies is being freed of bottlenecks and now runs stably up to 1 Hz. Early tests have already shown that bimorph mirrors can repeatedly switch the size of an X-ray beam in well under 10 seconds. Bimorph mirrors at synchrotron beamlines are now growing beyond the largely static operation of the past and gaining a new dynamism through development projects that are now well advanced. We report on how these endeavours will make it easier for beamlines to utilise the full potential of bimorph mirrors.